2013
DOI: 10.1128/jvi.00381-13
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Cocirculation of Stable Subtypes, Emerging Lineages, and New Sporadic Reassortants of Porcine Influenza Viruses in Swine Populations in Northwest Germany

Abstract: The emergence of the human 2009 pandemic H1N1 (H1N1pdm) virus from swine populations refocused public and scientific attention on swine as an important source of influenza A viruses bearing zoonotic potential. Widespread and year-round circulation of at least four stable lineages of porcine influenza viruses between 2009 and 2012 in a region of Germany with a high-density swine population is documented here. European avian influenza virus-derived H1N1 (H1N1av) viruses dominated the epidemiology, followed by hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 59 publications
15
59
0
1
Order By: Relevance
“…However, given our findings, and observations of new reassortant strains elsewhere in Europe47, 48, there should be no assumption that reassortment with possible zoonotic risk could not also occur in industrialised settings.…”
Section: Discussionmentioning
confidence: 58%
“…However, given our findings, and observations of new reassortant strains elsewhere in Europe47, 48, there should be no assumption that reassortment with possible zoonotic risk could not also occur in industrialised settings.…”
Section: Discussionmentioning
confidence: 58%
“…The pH1N1 virus has established itself as the dominant circulating seasonal H1N1 virus, and based on extensive surveillance studies in swine, reverse zoonosis has been identified worldwide (10)(11)(12)(13)(14)(15)(16)(17). pH1N1 harbors the ability to be transmitted very efficiently from human to human based on transmission analyses from the 2009 outbreak and detailed ferret transmission studies (73).…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence of 2009 pandemic pH1N1 virus, reverse zoonosis to swine has been globally observed (7)(8)(9)(10)(11)(12)(13)(14). North American classical swine viruses, European or Eurasian avian virus-like swine viruses, and triple reassortment of internal gene (TRIG) swine viruses cocirculate in swine populations today (15).…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the generation of novel escape mutants could gradually lead to the replacement of circulating virus strains (19,20), further complicating the antigenic and genetic evolution of swine IAVs. The occurrence of such antigenic drift events in swine is well documented (7,21,22). To develop an effective and robust swine IAV vaccination program, a rapid and robust method for antigenic characterization in swine is needed.…”
mentioning
confidence: 99%